Relationship between Students’ Gender and their Use of Politeness Strategies in the “Results and Discussions Section” of PhD Dissertations - Koohzad, Arezoo; Ghonsooly, Behzad; Ghapanchi, Zargham; Gholami, Reza (Dinamika Ilmu, 2019)
The researcher analyzed the Result and Discussion Sections of 10 dissertations of Iranian PhD students and 10 British PhD students by aiming to investigate their use of politeness strategies using Brown and Levinson’s (1987) taxonomy and its relationship with the gender of the authors. The results proved that Iranian writers most frequently used negative politeness strategies, followed by positive politeness strategies. British writers, like Iranians, used negative politeness strategies more than the others. The next frequent strategy was positive politeness strategies. Moreover, there was a significant difference between the frequency of politeness strategies used by Persian and British writers. Considering the gender, there is a significant difference between the positive strategies used by male and female Iranians. In fact, unlike the Male Iranian authors who used more positive strategies, the female Iranian authors used fewer strategies and this difference was significant. However, that there was no significant difference between the positive strategies used by British male and female participants. Also, there was a significant difference between the negative strategies used by male and female Iranians. In fact, the results show that the female Iranian authors used fewer strategies and this difference was significant. Moreover, there was a significant difference between the negative strategies used by British male and female participants.